A multi-layer PTFE copper-clad laminate and preparation method thereof

Through multi-layer structure design and optimization of filler distribution, combined with large-size high-thermal conductivity filler and silicon nitride, the thermal failure problem of copper clad plate in high heat flow density and high temperature environment is solved, and high thermal conductivity and excellent bonding performance are achieved to meet the needs of high-frequency and high-power electronic equipment.

CN119502484BActive Publication Date: 2025-04-04SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510060813.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Existing copper clad materials are prone to thermal failure under high heat flow density and high temperature environments, resulting in degradation or failure of equipment performance, and it is difficult to achieve high thermal conductivity and excellent bonding properties at the same time.

Method used

It adopts a multi-layer structural design, including a copper foil layer, a high bonding thermal conductivity layer, a high thermal resistance tear layer and another high bonding thermal conductivity layer. It uses large-size high thermal conductivity fillers such as spherical boron nitride and silicon nitride to form an efficient thermal conductivity network and strong binding force by optimizing the filler distribution and hierarchy structure.

Benefits of technology

It achieves high thermal conductivity (up to 3.47 W/m K) and high bonding performance (up to 1.62 N/mm) of copper clad plate, while reducing dielectric loss and thermal expansion coefficient, meeting the heat dissipation, stability and signal transmission requirements of high-frequency and high-power electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502484B_ABST
    Figure CN119502484B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of materials, and in particular to a multi-layer PTFE copper-clad laminate and a preparation method thereof. The PTFE copper-clad laminate of the present invention comprises an outermost copper foil layer, an intermediate high thermal conductivity tear-resistant layer, and a high bonding thermal conductive layer between the outermost copper foil layer and the intermediate high thermal conductivity tear-resistant layer. The PTFE copper-clad laminate of the present invention has high thermal conductivity, high bonding performance, and low dielectric loss, and is suitable for high-frequency, high-speed, high-power radio frequency microwave environments, ensuring stable transmission of high-frequency signals and long-term safe operation of devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a multi-layer PTFE copper-clad plate and a preparation method thereof. Background Art

[0002] As electronic devices develop towards higher frequencies, higher powers, smaller sizes and higher integration, traditional copper clad laminate materials have gradually been unable to meet increasingly stringent technical requirements. As a key basic material in high-frequency, high-power electronic devices, the thermal conductivity, bonding properties and electrical properties of copper clad laminates have a crucial impact on the long-term stability and reliability of the devices. Traditional copper clad laminate materials are prone to thermal failure under high heat flux and high temperature environments, resulting in reduced equipment performance or even failure. Therefore, the development of a copper clad laminate material with both high thermal conductivity and excellent bonding properties is a technical problem that needs to be overcome in order to improve the performance of electronic devices.

[0003] At present, introducing inorganic fillers into polymer substrates is a common method to improve the comprehensive performance of composite materials. The fillers are evenly distributed in the polymer by direct blending, and the composite substrate is obtained by hot pressing. This method is simple to operate, but there is an inherent contradiction between the thermal conductivity and bonding properties of the prepared copper clad laminate. This is because a high content of inorganic fillers is usually added to significantly improve the thermal conductivity, but as the filler content continues to increase, the interface defects between the filler and the matrix increase, the strength of the material body decreases, and even part of the filler will be exposed on the surface of the composite substrate, weakening the bonding force between the substrate and the copper foil, and eventually causing delamination or debonding, affecting the reliability of the copper clad laminate.

[0004] In response to this contradiction, existing research attempts to improve it through multi-layer structure design. For example, patent CN218804522U alternately stacks thermal conductive layers and adhesive layers to achieve a copper clad laminate design with a thermal conductivity ≥ 0.9 W / m K and an adhesive strength ≥ 1.0 N / mm; patent CN218777246U introduces an adhesive layer between the copper foil and the resin layer to obtain a copper clad laminate material with high thermal conductivity and stable structure (thermal conductivity ≥ 0.4 W / m K, peel strength ≥ 1.0 N / mm). However, there are still many deficiencies and difficulties in the performance improvement and practical application of multilayer structure design: on the one hand, there are limitations on the thermal conductivity of the bonding layer. The bonding layer is usually composed of pure polymer materials, and its large thermal resistance significantly limits the improvement of the overall thermal conductivity of the copper clad laminate; on the other hand, there is the influence of the heterogeneous interface of the thermal conductive layer. After introducing a high content of inorganic fillers into the thermal conductive layer, although a thermal conductive network can be formed, a large number of heterogeneous interfaces between the filler and the polymer matrix will aggravate phonon scattering, and the intrinsic high thermal conductivity of the filler cannot be fully utilized. At the same time, these interfaces may also weaken the mechanical strength and durability of the material. Based on the existing technology, it is basically difficult to achieve the preparation of high-frequency and high-power copper clad laminates with thermal conductivity ≥2 W / m K and bonding strength ≥1.5 N / mm, which cannot fully meet the stringent requirements of high-frequency and high-power electronic devices.

[0005] To achieve high-performance copper-clad laminate development, it is necessary to systematically solve the contradiction between thermal conductivity and bonding performance, and focus on breaking through the following technical difficulties: First, optimize the structure and composition of the bonding layer to ensure the bonding strength with the copper foil while reducing the negative impact of the bonding layer on the overall thermal conductivity of the copper-clad laminate; second, reasonably design the shape, size and distribution of the thermal conductive filler, build a complete thermal conductive path, reduce the phonon scattering of the heterogeneous interface between the filler and the matrix, and ensure that the material has a certain body strength and stability. Therefore, the development of high-performance copper-clad laminates with high thermal conductivity and high bonding to meet the needs of heat dissipation and stability of high-frequency, high-power electronic equipment is an urgent problem to be solved in this field. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a multilayer PTFE copper-clad laminate. The multilayer PTFE copper-clad laminate has a total of 5 layers, which are copper foil layer-high bonding thermal conductive layer-high thermal conductive tear-resistant layer-high bonding thermal conductive layer-copper foil layer in the following order; wherein the high thermal conductive tear-resistant layer is mainly prepared from a first filler and PTFE, and the high bonding thermal conductive layer is mainly prepared from a second filler and PTFE; the first filler is a large-sized high thermal conductive filler and an optional other filler A, and the large-sized high thermal conductive filler is selected from any one or more combinations of boron nitride, graphene, graphene oxide, silicon nitride, silicon carbide, aluminum oxide, and aluminum nitride with a D50 of 100-500 μm; the second filler is silicon nitride and an optional other filler B; the ratio of the thickness of the high thermal conductive tear-resistant layer to the total thickness of the two layers of high bonding thermal conductive layers is 4~6: 0.5~1.

[0007] Preferably, in the above multi-layer PTFE copper-clad laminate, the D50 of the large-sized high thermal conductivity filler is 100-200 μm.

[0008] Preferably, in the above multi-layer PTFE copper-clad laminate, the large-sized high thermal conductivity filler is boron nitride with a D50 of 100-500 μm.

[0009] Specifically, in the above multi-layer PTFE copper-clad laminate, the large-sized high thermal conductivity filler is spherical boron nitride with a D50 of 100-500 μm, assembled from hexagonal boron nitride, and more preferably 100-200 μm.

[0010] Preferably, in the above-mentioned multilayer PTFE copper-clad laminate, the other filler A is selected from any one or more combinations of flake boron nitride, silicon dioxide, titanium dioxide, silicon nitride, silicon carbide, graphene, graphene oxide, barium titanate, aluminum oxide, and aluminum nitride. Further preferably, the other filler A is selected from any one or a combination of two of silicon dioxide and titanium dioxide.

[0011] Preferably, in the above-mentioned multi-layer PTFE copper-clad laminate, the volume percentage of the first filler in the high thermal conductivity and tear-resistant layer is 20-60%.

[0012] Furthermore, in the above multi-layer PTFE copper-clad laminate, the volume percentage of the large-sized high thermal conductivity filler in the high thermal conductivity tear-resistant layer is 5-60%, preferably 30-40%.

[0013] Preferably, in the above multilayer PTFE copper-clad laminate, the other filler B is selected from any one or more combinations of silicon dioxide, titanium dioxide, boron nitride, barium titanate, aluminum oxide, and aluminum nitride. Further preferably, the other filler B is selected from boron nitride.

[0014] Preferably, in the above-mentioned multi-layer PTFE copper-clad laminate, the volume percentage of the second filler in the high-adhesion thermal conductive layer is 10-40%.

[0015] Furthermore, in the above multi-layer PTFE copper-clad laminate, the volume percentage of silicon nitride in the high-adhesion thermal conductive layer is 10-40%, preferably 30%.

[0016] Furthermore, in the above multi-layer PTFE copper-clad laminate, the first filler is a first filler that has been surface treated.

[0017] Furthermore, in the above multi-layer PTFE copper-clad laminate, the second filler is a second filler that has been surface treated.

[0018] Furthermore, in the above-mentioned multilayer PTFE copper-clad laminate, the surface treatment agent used for the surface treatment is selected from one or more of fluorine-containing surfactants, silane coupling agents, borate coupling agents, phosphate coupling agents, and titanate coupling agents.

[0019] Furthermore, in the above multi-layer PTFE copper-clad laminate, based on the mass of the filler to be treated being 100%, the mass of the surface treatment agent is 0.3-1.5%.

[0020] Specifically, in the above multi-layer PTFE copper-clad laminate, the thickness of the high thermal conductivity and tear resistance layer is 500-1000 μm.

[0021] Specifically, in the above multi-layer PTFE copper-clad laminate, the single layer thickness of the high-adhesion thermal conductive layer is 50-100 μm.

[0022] Specifically, in the above multi-layer PTFE copper-clad laminate, the thickness of the copper foil is 20-50 μm.

[0023] The present invention also provides a method for preparing the multilayer PTFE copper-clad laminate. The method comprises the following steps:

[0024] (1) Weigh PTFE, a first filler and deionized water in proportion, homogenize and degas, and obtain a mixed slurry C; weigh PTFE, a second filler and deionized water in proportion, homogenize and degas, and obtain a mixed slurry D;

[0025] (2) coating the mixed slurry C and the mixed slurry D obtained in step (1) into films respectively, and drying and sintering them to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg respectively;

[0026] (3) The layers of materials are stacked in the order of copper foil-high adhesion thermal conductive layer-high thermal conductive tear resistant layer-high adhesion thermal conductive layer-copper foil, and the multilayer PTFE copper clad laminate is obtained after vacuum hot pressing.

[0027] Preferably, in step (1) of the method for preparing the multilayer PTFE copper-clad laminate, the content of deionized water in the mixed slurry C or the mixed slurry D is 40-50 wt %.

[0028] Preferably, in step (2) of the method for preparing the multilayer PTFE copper-clad laminate, the drying is controlled at a temperature of 40-60°C for 20-30 min, and the sintering is controlled at a temperature of 370-380°C for 15-20 min.

[0029] Preferably, in step (3) of the method for preparing the multilayer PTFE copper-clad laminate, the pressure of the hot pressing control is 200-1000 psi, the temperature is 370-380°C, and the time is 1-2 h.

[0030] Beneficial effects:

[0031] The present invention uses a large-size high thermal conductivity filler such as spherical boron nitride as the main filling filler of the high thermal conductivity tear-resistant layer and a high bonding thermal conductive layer with silicon nitride as the main filling filler, and the dielectric layer formed by the specific order and thickness design, by introducing a large-size high thermal conductivity filler such as spherical boron nitride and optimizing the filler distribution, forming an efficient thermal conductive network, reducing interface defects and phonon scattering, so that the prepared PTFE copper-clad laminate has high thermal conductivity and high bonding performance, solves the contradiction between thermal conductivity and bonding performance of traditional copper-clad laminates in high-frequency and high-power environments, and by reasonably selecting the type of inorganic filler, extremely low dielectric loss and thermal expansion coefficient are achieved at the same time, meeting the needs of high-frequency, high-power electronic equipment heat dissipation, stability, signal transmission, safety, etc. The thermal conductivity of the PTFE copper-clad laminate of the present invention can reach 3.47 W / m K, the bonding performance can reach 1.62 N / mm, the dielectric loss is 0.0004, and the thermal expansion coefficient is less than 45ppm / K. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the structure of the multilayer PTFE copper-clad laminate of the present invention DETAILED DESCRIPTION

[0033] The invention provides a multi-layer PTFE copper-clad laminate, comprising an outermost copper foil layer, a middlemost high thermal conductivity tear-resistant layer, and a high-bonding thermal conductive layer therebetween; the middlemost high thermal conductivity tear-resistant layer is prepared with a large-size high thermal conductivity filler as a main filler and PTFE as a matrix, and has excellent thermal conductivity and bulk strength; the high-bonding thermal conductive layer is prepared with silicon nitride as a main filler and PTFE as a matrix, and exhibits strong bonding with the copper foil and good thermal conductivity.

[0034] In the multilayer PTFE copper-clad laminate of the present invention, the high thermal conductivity tear-resistant layer is mainly filled with large-sized high thermal conductivity fillers such as spherical boron nitride. The large-sized spherical boron nitride itself has a perfect thermal conduction path. During the material preparation process, the spherical boron nitrides are mutually squeezed and interlocked to form a three-dimensional continuous thermal conduction path in the dielectric layer. The contact interface between the large-sized spherical boron nitride and the PTFE matrix is ​​relatively small, reducing the phonon scattering at the interface, thereby ensuring high thermal conductivity; and the spherical boron nitride in the high thermal conductivity tear-resistant layer has a stress dispersion effect, which can resist tearing during the peeling process, thereby ensuring its own structural strength. The high bonding thermal conductive layer is mainly filled with silicon nitride and the filling content is relatively low, forming a good bonding effect with copper foil, ensuring high bonding performance, and the addition of inorganic fillers helps to improve its own thermal conductivity, reducing the negative impact of the high bonding thermal conductive layer on thermal conductivity. At the same time, the inherent bandgap width of spherical boron nitride and silicon nitride is large, which fundamentally suppresses the polarization under the electric field and ensures low dielectric loss. Therefore, the multi-layer PTFE copper-clad laminate of the present invention fully meets the heat dissipation, stability and signal transmission requirements of high-frequency and high-power electronic equipment.

[0035] In the multilayer PTFE copper-clad laminate of the present invention, the large-size high thermal conductivity filler used in the high thermal conductivity tear-resistant layer is selected from any one or more combinations of boron nitride, graphene, graphene oxide, silicon nitride, silicon carbide, aluminum oxide, and aluminum nitride with a D50 of 100-500 μm, preferably D50 of 100-200 μm. For large-size high thermal conductivity fillers, they can be purchased directly on the market, or prepared by existing conventional methods, such as assembling them using corresponding original raw materials, such as assembling hexagonal boron nitride as a raw material into spherical boron nitride particles, assembling spherical graphene particles using graphene sheets as raw materials, assembling spherical graphene oxide particles using graphene oxide as raw materials, assembling silicon nitride particles using silicon nitride as raw materials, assembling spherical silicon carbide particles using silicon carbide as raw materials, assembling spherical aluminum oxide particles using aluminum oxide as raw materials, and assembling spherical aluminum nitride particles using aluminum nitride as raw materials. The large-sized high thermal conductive filler of the present invention preferably adopts spherical boron nitride with a D50 of 100-500 μm, and can be assembled using hexagonal boron nitride as a raw material, preferably with a D50 of 100-200 μm. In the present invention, except for the large-sized high thermal conductive filler, there is no special requirement for the size of other fillers.

[0036] In the multi-layer PTFE copper-clad laminate of the present invention, the ratio of the thickness of the high thermal conductivity anti-tearing layer to the total thickness of the two high-bonding thermal conductive layers is 4-6:0.5-1, which can further reduce the influence of the low thermal conductivity of the high-bonding thermal conductive layer on the overall thermal conductivity of the dielectric layer, thereby ensuring the high thermal conductivity of the copper-clad laminate.

[0037] In the multi-layer PTFE copper-clad laminate of the present invention, the aforementioned fillers may be added or not added. For example, the aforementioned other fillers A may be added or not added.

[0038] The material information involved in the following examples is as follows:

[0039] (1) PTFE resin: PTFE emulsion, brand 331z, solid content 60%, produced by Shandong Dongyue Polymer Material Co., Ltd.; It should be noted that in the following embodiments of the present invention, the volume percentage of PTFE in the PTFE composite material is calculated based on the solid content of the PTFE emulsion, and does not include the solvent in the emulsion.

[0040] (2) Thickener: polyoxyethylene distyrenated anisole, EMULGEN A-60 from Kao Corporation.

[0041] Example 1

[0042] A multilayer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate high thermal conductivity tear-resistant layer and a high bonding thermal conductive layer in between. The high thermal conductivity tear-resistant layer comprises the following components by volume fraction: 50% PTFE resin, 40% spherical boron nitride (average particle size D50 is 120 μm), 7.5% silicon dioxide (average particle size is 10 μm), and 2.5% titanium dioxide (average particle size is 10 μm). The high bonding thermal conductive layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size is 10 μm), and 4% flaky boron nitride (average particle size is 30 μm).

[0043] The preparation method is as follows:

[0044] (1) According to the formula content of the high thermal conductivity tear-resistant layer and the high bonding thermal conductive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until it is uniform and degassed;

[0045] (2) After the uniformly mixed adhesive obtained in step (1) is coated into a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg;

[0046] (3) The layers of materials were stacked in the order of copper foil - high adhesion thermal conductive layer (80 μm) - high thermal conductive tear resistant layer (1000 μm) - high adhesion thermal conductive layer (80 μm) - copper foil, and vacuum hot pressed with an applied pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper clad laminate.

[0047] Example 2

[0048] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate high thermal conductivity tear-resistant layer and a high bonding thermal conductive layer in between. The high thermal conductivity tear-resistant layer comprises the following components by volume fraction: 60% PTFE resin, 30% spherical boron nitride (average particle size D50 is 120 μm), 7.5% silicon dioxide (average particle size is 10 μm), and 2.5% titanium dioxide (average particle size is 10 μm). The high bonding thermal conductive layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size is 10 μm), and 4% flaky boron nitride (average particle size is 30 μm).

[0049] The preparation method is as follows:

[0050] (1) According to the formula content of the high thermal conductivity tear-resistant layer and the high bonding thermal conductive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until it is uniform and degassed;

[0051] (2) After the uniformly mixed adhesive obtained in step (1) is coated into a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg;

[0052] (3) The layers of materials were stacked in the order of copper foil - high adhesion thermal conductive layer (80 μm) - high thermal conductive tear resistant layer (1000 μm) - high adhesion thermal conductive layer (80 μm) - copper foil, and vacuum hot pressed with an applied pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper clad laminate.

[0053] Example 3

[0054] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate high thermal conductivity tear-resistant layer and a high bonding thermal conductive layer in between. The high thermal conductivity tear-resistant layer comprises the following components by volume fraction: 50% PTFE resin, 40% spherical boron nitride (average particle size D50 is 150 μm), 7.5% silicon dioxide (average particle size is 10 μm), and 2.5% titanium dioxide (average particle size is 10 μm). The high bonding thermal conductive layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size is 10 μm), and 4% flaky boron nitride (average particle size is 30 μm).

[0055] The preparation method is as follows:

[0056] (1) According to the formula content of the high thermal conductivity tear-resistant layer and the high bonding thermal conductive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until it is uniform and degassed;

[0057] (2) After the uniformly mixed adhesive obtained in step (1) is coated into a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg;

[0058] (3) The layers of materials were stacked in the order of copper foil - high adhesion thermal conductive layer (80 μm) - high thermal conductive tear resistant layer (1000 μm) - high adhesion thermal conductive layer (80 μm) - copper foil, and vacuum hot pressed with an applied pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper clad laminate.

[0059] Example 4

[0060] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate high thermal conductivity tear-resistant layer and a high bonding thermal conductive layer in between. The high thermal conductivity tear-resistant layer comprises the following components by volume fraction: 60% PTFE resin, 30% spherical boron nitride (average particle size D50 is 150 μm), 7.5% silicon dioxide (average particle size is 10 μm), and 2.5% titanium dioxide (average particle size is 10 μm). The high bonding thermal conductive layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size is 10 μm), and 4% flaky boron nitride (average particle size is 30 μm).

[0061] The preparation method is as follows:

[0062] (1) According to the formula content of the high thermal conductivity tear-resistant layer and the high bonding thermal conductive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until it is uniform and degassed;

[0063] (2) After the uniformly mixed adhesive obtained in step (1) is coated into a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg;

[0064] (3) The layers of materials were stacked in the order of copper foil - high adhesion thermal conductive layer (80 μm) - high thermal conductive tear resistant layer (1000 μm) - high adhesion thermal conductive layer (80 μm) - copper foil, and vacuum hot pressed with an applied pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper clad laminate.

[0065] Example 5

[0066] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate high thermal conductivity tear-resistant layer and a high bonding thermal conductive layer in between. The high thermal conductivity tear-resistant layer comprises the following components by volume fraction: 50% PTFE resin, 40% spherical boron nitride (average particle size of 120 μm), 7.5% silicon dioxide (average particle size of 10 μm), and 2.5% titanium dioxide (average particle size of 10 μm). The high bonding thermal conductive layer comprises the following components by volume fraction: 60% PTFE resin, 40% silicon nitride (average particle size of 10 μm)

[0067] The preparation method is as follows:

[0068] (1) According to the formula content of the high thermal conductivity tear-resistant layer and the high bonding thermal conductive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until it is uniform and degassed;

[0069] (2) After the uniformly mixed adhesive obtained in step (1) is coated into a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg;

[0070] (3) The layers of materials were stacked in the order of copper foil - high adhesion thermal conductive layer (80 μm) - high thermal conductive tear resistant layer (1000 μm) - high adhesion thermal conductive layer (80 μm) - copper foil, and vacuum hot pressed with an applied pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper clad laminate.

[0071] Comparative Example 1

[0072] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate heat-conducting layer and a bonding layer therebetween. The heat-conducting layer comprises the following components by volume fraction: 50% PTFE resin, 40% spherical boron nitride (average particle size of 40 μm), 7.5% silicon dioxide (average particle size of 10 μm), and 2.5% titanium dioxide (average particle size of 10 μm). The bonding layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size of 10 μm), and 4% flaky boron nitride (average particle size of 30 μm).

[0073] The preparation method is as follows:

[0074] (1) According to the formula content of the thermal conductive layer and the adhesive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until the mixture is uniform and degassed;

[0075] (2) After the uniformly mixed adhesive obtained in step (1) is coated to form a film, the moisture is dried in an oven at 60°C, and then sintered in a high-temperature oven at 370°C to obtain a thermal conductive layer prepreg and a bonding layer prepreg.

[0076] (3) The material layers were stacked in the order of copper foil - adhesive layer (80 μm) - thermal conductive layer (1000 μm) - adhesive layer (80 μm) - copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper-clad laminate.

[0077] Comparative Example 2

[0078] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate heat-conducting layer and a bonding layer therebetween. The heat-conducting layer comprises the following components by volume fraction: 50% PTFE resin, 40% spherical boron nitride (average particle size of 80 μm), 7.5% silicon dioxide (average particle size of 10 μm), and 2.5% titanium dioxide (average particle size of 10 μm). The bonding layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size of 10 μm), and 4% flaky boron nitride (average particle size of 30 μm).

[0079] The preparation method is as follows:

[0080] (1) According to the formula content of the thermal conductive layer and the adhesive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until the mixture is uniform and degassed;

[0081] (2) After the uniformly mixed adhesive obtained in step (1) is coated into a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a thermal conductive layer prepreg and a bonding layer prepreg.

[0082] (3) The materials were stacked in the order of copper foil - adhesive layer (80 μm) - thermal conductive layer (1000 μm) - adhesive layer (80 μm) - copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370 °C, and a lamination time of 1 h to obtain a multilayer PTFE copper-clad laminate.

[0083] Comparative Example 3

[0084] A multi-layer PTFE copper-clad laminate comprises a copper foil (1 oz), an intermediate heat-conducting layer and a bonding layer therebetween. The heat-conducting layer comprises the following components by volume fraction: 50% PTFE resin, 40% flake hexagonal boron nitride (average particle size of 30 μm), 7.5% silicon dioxide (average particle size of 10 μm), and 2.5% titanium dioxide (average particle size of 10 μm). The bonding layer comprises the following components by volume fraction: 60% PTFE resin, 36% silicon nitride (average particle size of 10 μm), and 4% flake boron nitride (average particle size of 30 μm).

[0085] The preparation method is as follows:

[0086] (1) According to the formula content of the thermal conductive layer and the adhesive layer, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and the mixture is mixed in a homogenizer for 20 minutes until the mixture is uniform and degassed;

[0087] (2) After the uniformly mixed adhesive obtained in step (1) is coated to form a film, the moisture is dried in an oven at 60°C, and then sintered in a high-temperature oven at 370°C to obtain a thermal conductive layer prepreg and a bonding layer prepreg.

[0088] (3) The material layers were stacked in the order of copper foil - adhesive layer (80 μm) - thermal conductive layer (1000 μm) - adhesive layer (80 μm) - copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a multilayer PTFE copper-clad laminate.

[0089] Comparative Example 4

[0090] A PTFE copper-clad laminate comprises a copper foil (1 oz) and an intermediate dielectric layer, wherein the dielectric layer comprises the following components by volume fraction: 50% of PTFE resin, 40% of spherical boron nitride (with an average particle size of 120 μm), 7.5% of silicon dioxide (with an average particle size of 10 μm), and 2.5% of titanium dioxide (with an average particle size of 10 μm).

[0091] The preparation method is as follows:

[0092] (1) According to the formula content, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and mixed in a homogenizer for 20 minutes until uniform and defoamed;

[0093] (2) After the uniformly mixed adhesive obtained in step (1) is coated to form a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a prepreg;

[0094] (3) The materials are stacked in the order of copper foil-semi-cured sheet (250 μm)-copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a PTFE copper clad laminate.

[0095] Comparative Example 5

[0096] A PTFE copper-clad laminate comprises a copper foil (1 oz) and an intermediate dielectric layer, wherein the dielectric layer comprises the following components by volume fraction: 50% of PTFE resin, 40% of flaky hexagonal boron nitride (with an average particle size of 30 μm), 7.5% of silicon dioxide (with an average particle size of 10 μm), and 2.5% of titanium dioxide (with an average particle size of 10 μm).

[0097] The preparation method is as follows:

[0098] (1) According to the formula content, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and mixed in a homogenizer for 20 minutes until uniform and defoamed;

[0099] (2) After the uniformly mixed adhesive obtained in step (1) is coated to form a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a prepreg;

[0100] (3) The materials are stacked in the order of copper foil-semi-cured sheet (250 μm)-copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a PTFE copper clad laminate.

[0101] Comparative Example 6

[0102] A PTFE copper-clad laminate comprises a copper foil (1 oz) and an intermediate dielectric layer, wherein the dielectric layer comprises the following components by volume fraction: 60% of PTFE resin, 36% of silicon nitride (with an average particle size of 10 μm), and 4% of flaky hexagonal boron nitride (with an average particle size of 30 μm).

[0103] The preparation method is as follows:

[0104] (1) According to the formula content, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and mixed in a homogenizer for 20 minutes until uniform and defoamed;

[0105] (2) After the uniformly mixed adhesive obtained in step (1) is coated to form a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a prepreg;

[0106] (3) The materials are stacked in the order of copper foil-semi-cured sheet (250 μm)-copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a PTFE copper clad laminate.

[0107] Comparative Example 7

[0108] A PTFE copper-clad laminate comprises a copper foil (1 oz) and an intermediate dielectric layer, wherein the dielectric layer comprises the following components by volume fraction: 60% of PTFE resin and 40% of silicon nitride (with an average particle size of 10 μm).

[0109] The preparation method is as follows:

[0110] (1) According to the formula content, the filler and PTFE are mixed evenly in deionized water, and then an appropriate amount of thickener is added, and mixed in a homogenizer for 20 minutes until uniform and defoamed;

[0111] (2) After the uniformly mixed adhesive obtained in step (1) is coated to form a film, the moisture is dried in an oven at 60° C., and then sintered in a high-temperature oven at 370° C. to obtain a prepreg;

[0112] (3) The materials are stacked in the order of copper foil-semi-cured sheet (250 μm)-copper foil, and vacuum hot pressed with a pressure of 400 psi, a maximum temperature of 370°C, and a lamination time of 1 h to obtain a PTFE copper clad laminate.

[0113] The performance test of the copper clad laminates prepared in Examples 1-5 and Comparative Examples 1-7 was performed as follows:

[0114] (1) Thermal conductivity: tested using ASTM D5470 standard.

[0115] (2) Peel strength: tested using IPC-TM-650 2.4.8 standard.

[0116] (3) Dielectric loss: Tested using IPC-TM-650 2.5.5.5 standard.

[0117] (4) Thermal expansion coefficient: tested using IPC-TM-650 2.4.24 method.

[0118] The test results are shown in Table 1:

[0119] Table 1

[0120] sample Thermal conductivity (W / m K) Peel strength (N / mm) Dielectric loss Thermal expansion coefficient (ppm / K) Example 1 3.47 1.62 0.0004 44.6 Example 2 2.67 1.80 0.00035 50.3 Example 3 3.51 1.58 0.00042 35.4 Example 4 2.72 1.76 0.00031 40.1 Example 5 3.37 1.43 0.00044 51.1 Comparative Example 1 3.13 0.75 0.0007 50.6 Comparative Example 2 3.20 0.82 0.0005 48.3 Comparative Example 3 2.05 0.56 0.0008 65.2 Comparative Example 4 2.03 1.1 0.0008 36.9 Comparative Example 5 1.71 0.64 0.0003 65.4 Comparative Example 6 1.11 1.94 0.0008 43.9 Comparative Example 7 0.91 1.78 0.0012 89.7

[0121] As can be seen from Table 1, the multilayer PTFE copper clad laminate provided by the present invention effectively improves the thermal conductivity and bonding properties of the PTFE copper clad laminate by designing a multilayer structure of copper foil-high bonding thermal conductive layer-high thermal conductive tearing resistant layer-high bonding thermal conductive layer-copper foil, so that the thermal conductivity of Example 1 can reach 3.47 W / m K, and the bonding performance reaches 1.62 N / mm; at the same time, inorganic fillers such as spherical boron nitride, silicon nitride, silicon dioxide, and titanium dioxide are selected to ensure low dielectric loss and low thermal expansion coefficient of the copper clad laminate, the dielectric loss is ≤0.0004, and the thermal expansion coefficient is ≤45 ppm / K, which meets the heat dissipation, stability and signal transmission requirements of high-frequency and high-power electronic equipment.

[0122] Comparison of Examples 1 and 3 with Comparative Examples 1 and 2 shows that large-sized spherical boron nitride (D50 = 120 μm, D50 = 150 μm) has higher bonding performance than small-sized spherical boron nitride (D50 = 40 μm, D50 = 80 μm). This is because only by introducing a small amount of filler-matrix interface and filler-filler interface can the bulk strength of the middle high thermal conductivity tear-resistant layer be guaranteed, and the damage to the material body caused by the concentration of stress in interface defects be reduced.

[0123] Examples 1 and 3 show higher thermal conductivity and peel strength than Comparative Example 3. This is because the spherical boron nitride selected as the filler of the intermediate high thermal conductivity tear-resistant layer introduces a complete thermal conduction path and fewer interfaces compared to the flaky hexagonal boron nitride, reducing phonon scattering and stress concentration. The flaky hexagonal boron nitride tends to be horizontally oriented during the coating process, reducing the out-of-plane thermal conductivity growth rate and introducing surface defects in the horizontal direction, which is prone to self-tearing.

[0124] Comparison of Examples 1 and 2 with Comparative Example 4 shows that the addition of the high-bonding thermal conductive layer effectively improves the bonding strength between the intermediate dielectric layer and the copper foil, and the bonding performance is effectively improved. At the same time, the multi-layer structure design increases the thickness of the intermediate high thermal conductive tear-resistant layer, and also improves the thermal conductivity of the PTFE copper clad laminate. This is because the spherical boron nitride has a larger particle size. When the thickness of the dielectric layer increases, more spherical boron nitride on the outside of the dielectric layer can form a more complete thermal conductive network structure, which significantly improves the thermal conductivity coefficient.

[0125] The peeling test failures of Examples 1-5 are all tearing failures of the high thermal conductivity tear-resistant layer, which also shows good adhesion between the high bonding thermal conductive layer and the copper foil. The measured peeling strength reflects the bonding ability of the thermal conductive filler and the PTFE matrix.

[0126] Comparing Examples 1 and 2 with Comparative Example 5, which is also the tearing of the PTFE composite material itself, it can be seen that the bonding between spherical boron nitride and PTFE is tighter than that between flaky hexagonal boron nitride and PTFE, and during the peeling process, flaky hexagonal boron nitride is more likely to form stress concentration and thus rupture between layers, resulting in lower bonding performance.

[0127] Compared with Comparative Examples 6 and 7, Examples 1-5 show that the high thermal conductivity and tear-resistant layer in the middle significantly improves the thermal conductivity of the PTFE copper clad laminate.

Claims

1. A multi-layer PTFE copper-clad laminate, characterized in that: The multilayer PTFE copper-clad laminate has a total of 5 layers, which are copper foil layer-high-bonding thermal conductive layer-high-bonding thermal conductive tear-resistant layer-high-bonding thermal conductive layer-copper foil layer in the following order; wherein the high-bonding thermal conductive tear-resistant layer is mainly prepared from a first filler and PTFE, and the high-bonding thermal conductive layer is mainly prepared from a second filler and PTFE; the first filler is a spherical large-size high-thermal conductive filler and an optional other filler A, and the spherical large-size high-thermal conductive filler is selected from any one or more combinations of boron nitride, graphene, graphene oxide, silicon nitride, silicon carbide, aluminum oxide, and aluminum nitride with a D50 of 100-500 μm; the second filler is silicon nitride and an optional other filler B; the ratio of the thickness of the high-thermal conductive tear-resistant layer to the total thickness of the two high-bonding thermal conductive layers is 4~6: 0.5~1.

2. The multilayer PTFE copper-clad laminate according to claim 1, characterized in that: The large-size high thermal conductivity filler is spherical boron nitride with a D50 of 100-200 μm, which is assembled from hexagonal boron nitride.

3. The multilayer PTFE copper-clad laminate according to claim 1 or 2, characterized in that: The other filler A is selected from any one or more combinations of flaky boron nitride, silicon dioxide, titanium dioxide, silicon nitride, silicon carbide, graphene, graphene oxide, barium titanate, aluminum oxide, and aluminum nitride.

4. The multilayer PTFE copper-clad laminate according to claim 1 or 2, characterized in that: The volume percentage of the first filler in the high thermal conductivity and tear resistant layer is 20-60%, and the volume percentage of the large-sized high thermal conductivity filler in the high thermal conductivity and tear resistant layer is 5-60%.

5. The multilayer PTFE copper-clad laminate according to claim 1 or 2, characterized in that: The other filler B is selected from any one or more combinations of silicon dioxide, titanium dioxide, boron nitride, barium titanate, aluminum oxide, and aluminum nitride.

6. The multilayer PTFE copper-clad laminate according to claim 1 or 2, characterized in that: The volume percentage of the second filler in the high-bonding thermal conductive layer is 10-40%, and the volume percentage of silicon nitride in the high-bonding thermal conductive layer is 10-40%.

7. The multilayer PTFE copper-clad laminate according to claim 1 or 2, characterized in that: The first filler and the second filler are both first fillers and second fillers that have been surface treated.

8. The multilayer PTFE copper-clad laminate according to claim 1 or 2, characterized in that: The thickness of the high thermal conductivity tear-resistant layer is 500-1000 μm, the single layer thickness of the high bonding thermal conductive layer is 50-100 μm, and the thickness of the copper foil is 20-50 μm.

9. The method for preparing the multilayer PTFE copper-clad laminate according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh PTFE, a first filler and deionized water in proportion, homogenize and degas, and obtain a mixed slurry C; weigh PTFE, a second filler and deionized water in proportion, homogenize and degas, and obtain a mixed slurry D; (2) coating the mixed slurry C and the mixed slurry D obtained in step (1) into films respectively, and drying and sintering them to obtain a high thermal conductivity tear-resistant layer prepreg and a high bonding thermal conductive layer prepreg respectively; (3) The layers of materials are stacked in the order of copper foil-high adhesion thermal conductive layer-high thermal conductive tear resistant layer-high adhesion thermal conductive layer-copper foil, and the multilayer PTFE copper clad laminate is obtained after vacuum hot pressing.

10. The method for preparing the multilayer PTFE copper-clad laminate according to claim 9, characterized in that: Satisfy at least one of the following: In step (1), the content of deionized water in the mixed slurry C or the mixed slurry D is 40-50wt%; In step (2), the drying is controlled at a temperature of 40-60°C and a time of 20-30 min; In step (2), the sintering temperature is controlled at 370-380°C and the sintering time is 15-20 min; In step (3), the hot pressing is controlled at a pressure of 200-1000 psi, a temperature of 370-380 °C, and a time of 1-2 h.

Citation Information

Patent Citations

  • Low-dielectric filler for copper-clad plate, preparation method of low-dielectric filler, intermediate layer of copper-clad plate and copper-clad plate

    CN114539626A

  • Low-dielectric-constant and high-thermal-conductivity type high-frequency metal foil-clad laminated board and manufacturing method thereof

    CN114905813A